Assessment Of Changes In Articular Eminence Inclination In Different Skeletal Malocclusions With Various Growth Pattern Using Orthopantomograms - Dutta, Sourabh; Bhardwaj, Madhvi; Yadav, Shweta; Singh , Aashi; Mahtab, Sana; Gupta, Sweety (Journal of Neonatal Surgery, 2025)
Introduction- The temporomandibular joint (TMJ) is a crucial component of the locomotor system, morphologically and functionally complex, facilitating a wide range of mandibular movements. A distinctive feature of TMJ is the articular eminence, a vital component influencing condylar movement , force transmission during masticatory loading.This study explores the changes in articular eminence inclination across different growth patterns and skeletal malocclusions using orthopantomograms. Objective- This study explores the changes in articular eminence inclination across different growth patterns and skeletal malocclusions using orthopantomograms. Methodology- This study was carried out in the Department of Orthodontics and Dentofacial Orthopaedics, Saraswati Dental College and Hospital in digitally acquired images from routinely taken Orthopantomograms which satisfied the inclusion criteria. The radiograph with lead acetate tracing sheet attached was viewed in a radiographic illuminator for marking the following landmarks using 3H pencil .The Angles α, β & γ were measured manually using protractors. The values of the following angles were categorized according to the different skeletal malocclusions and various growth patterns in the data sheet in Microsoft excel. Result- Three angles (alpha, beta, and gamma) representing different aspects of articular eminence inclination were measured and compared between classes. Significant differences were observed in horizontal growth patterns, indicating variations in mean angles among skeletal classes. However, in vertical and average growth patterns, differences were statistically insignificant. Conclusion-This study provides valuable insights into the association between articular eminence inclination, skeletal classes, and growth patterns. The horizontal growth pattern demonstrates significant variations, emphasizing the importance of considering these factors in understanding TMJ morphology